1978
DOI: 10.1192/bjp.132.5.487
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Duration of Treatment in a Therapeutic Community for Drug Abusers and Subsequent Criminality

Abstract: The conviction rates for the first 61 admissions to a therapeutic community for drug dependence were obtained for a period two years prior to admission and two years after discharge, by searching in the Criminal Records Office at Scotland Yards. A long-stay group (n = 20) which had remained in residence more than six months was compared with a medium-stay group (n = 20) which had remained from one to six months and a short stay group (n = 21) which had remained less than one month. The long-stay group had a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…De Leon 1973;. Although similar studies were carried out in some UK concept-based therapeutic communities (Ogbourne and Melotte 1977;Wilson and Mandelbrote 1978), the trend for such work there did not continue. In the USA however, evaluation research became central to the therapeutic community movement in the community (De Leon 1994) and in prisons (Wexler 1997).…”
Section: Historical Antecedentsmentioning
confidence: 98%
“…De Leon 1973;. Although similar studies were carried out in some UK concept-based therapeutic communities (Ogbourne and Melotte 1977;Wilson and Mandelbrote 1978), the trend for such work there did not continue. In the USA however, evaluation research became central to the therapeutic community movement in the community (De Leon 1994) and in prisons (Wexler 1997).…”
Section: Historical Antecedentsmentioning
confidence: 98%
“…This no doubt accounts for the high rate of early dischargeapproximately one-third of admissions discharge themselves within the first month. Secondly, in a follow-up study of all residents admitted in the first 2 years, a significant association was found between staying in the programme for longer than 6 months, and reduced criminality and drug injection after leaving (Wilson & Mandelbrote, 1978;Wilson, 1978). This indicates that real changes in behaviour, generalized beyond the programme, do take place.…”
Section: Interpretations Of Changementioning
confidence: 97%
“…Eighty residents whose intellectual level was assessed on admission on the WAIS obtained a mean IQ of 108.6, SD 11.1. Details of drug use for the first two years' admissions are reported elsewhere (Wilson & Mandelbrote, 1978). The predominant pattern was of polydrug abuse including opiates and taking by injection.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…In some cases, the founding directors of the TC combined their practical, therapeutic work with their own academic development [61][62][63] . Some researchers like Wilson, Mandelbrote, Uchtenhagen and ZimmerHöffl er already published in highly qualifi ed peer-reviewed journals [54,57,64] . In an extensive review study on the design and effectiveness of TC research in Europe between 1980-1997, there were found no European evaluation and outcome studies indexed in the ISI Web of Science, besides the American ones.…”
Section: Discussionmentioning
confidence: 99%